The Regularized Trace Formula of the Spectrum of a Dirichlet Boundary Value Problem with Turning Point - Zaki F. A. El-Raheem; A. H. Nasser (Abstract and Applied Analysis)
We calculate the regularized trace formula of the infinite sequence of eigenvalues for some version of a Dirichlet boundary value problem with turning points.